(untitled) - Buttrick, George Arthur (ed.); Harmon, Nolan B. (ed.); Knox, John (ed.); Terrien, Samuel (ed.) (Nashville, 1982)
.AB: The Holy Scriptures in the KJV and RSV with general articles and introduction, exegesis, exposition for each book of the Bible
Vol.6
Keywords: Harmon, Nolan B. (ed.); Buttrick, George Arthur (ed.); Knox, John (ed.); Bible-commentaries